The Relationship Between Leadership Style and Lifelong Learning of Employees (Journal of Universal Excellence, 2026)
Research Question (RQ): Lifelong learning is the basis of today's business. All employees, and their managers, in modern times, need to continuously learn and work on developing their abilities. Nevertheless, lifelong learning requires certain efforts, and support is needed throughout the process. The main problem of the research was the influence of different leadership styles on lifelong learning. The main question was leaders and leadership styles influence the lifelong learning of their employees and followers?Purpose: The main purpose of the research was to examine the relationship between leadership styles and lifelong learning of employees. The purpose was to see which leadership styles were most supportive of lifelong learning, that is, which leadership styles lead to the greatest motivation when it comes to lifelong learning of employees.Method: In the theoretical part of the work, previous research related to this topic were consulted. Empirical research has been done on a sample of 30 companies, small and medium-sized enterprises, an analysis of leadership styles in the analysed companies, an analysis of lifelong learning methods, and the relationship between leadership styles and lifelong learning was examined.Results: The research results indicate that the most represented leadership style in small and medium enterprises is democratic (56.7%). When it comes to supporting employees in the context of additional learning, the research results indicate that autocratic leaders are most often willing to support their employees through financial investments, while democratic leaders are more willing to provide their employees with days off to improve professionally. Also, the research results show that the approach to learning among employees is the most studious and better in cases where the leader is an autocrat, but the avoidance of learning is most present in cases where the leader is laissez-faire.Organization: Through the research, it was determined which leadership styles contributed most to the motivation for lifelong learning, and insight into such results could be an input for leaders (or those who intend to become leaders) on how to adapt their style in the context of the greatest motivation of employees towards lifelong learning.Society: More knowledge, or learning, surely leads to greater social responsibility. Through lifelong learning, not only employees’ benefit, but also managers, clients, consumers, and the wider social community.Originality: Research of this type is one of the most important in this region, where the connection between leadership styles and lifelong learning is sought on a sample of small and medium-sized enterprises.Limitations / further research: Research limitations refer to difficulties in the process of forming a sample and obtaining data. Recommendations for future research refer to the inclusion of additional variables in the existing constellation, among which are change management, quality, formal education.
Keywords: lifelong learning; leaders; leadership; managers; styles; recommendations; influence